Ethics and Law of Using Artificial Intelligence (AI) in Completing University Exams: An Islamic Legal Perspective - Ani Novi Anggraeni; Hana Hanifah Dwi Nastiti; Nabila Dwi Putri Lestari; Nabila Rossa Inriani; Rizqya Zuhra Annisa; Yulia Riska Mardenil; Edi Suresman (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of Artificial Intelligence (AI) in higher education presents both opportunities and challenges, particularly in the context of university examinations. This study aims to analyze the frequency of AI usage by students during exams and its impact on academic ethics from the perspective of Islamic law. The research employed a quantitative associative approach using a survey method involving 50 university students who had used AI in examinations. The research instrument consisted of a Likert-scale questionnaire measuring two variables: frequency of AI usage (X) and students’ academic ethics from the perspective of Islamic law (Y). The findings indicate that the mean score for AI usage frequency was 23.34, while the mean score for academic ethics was 33.14. Regression analysis revealed an R Square value of 0.309 with a negative regression coefficient (-0.288), indicating a significant negative relationship between the frequency of AI usage and students’ academic ethics. The higher the frequency of AI usage in examinations, the lower the level of academic ethics from an Islamic legal perspective. From the standpoint of Islamic law, the unauthorized use of AI during examinations may fall under the category of tadl?s (deception) and academic dishonesty, which contradicts the principles of Sidq (honesty), amanah (trustworthiness), and the objectives of Islamic law. Although students demonstrate a relatively high awareness of academic ethics, increasing dependency on AI poses a risk of diminishing academic integrity. Therefore, a clear sharia-based framework is necessary to ensure that AI technology is utilized within ethical and Islamic boundaries while maintaining academic integrity.